2014
DOI: 10.1107/s2053230x13034584
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization and preliminary X-ray crystallographic studies of dipeptidyl aminopeptidase BII from Pseudoxanthomonas mexicana WO24

Abstract: Dipeptidyl aminopeptidase BII from Pseudoxanthomonas mexicana WO24 (DAP BII) is able to cleave a variety of dipeptides from the amino-terminus of substrate peptides. For crystallographic studies, DAP BII was overproduced in Escherichia coli, purified and crystallized using the hanging-drop vapourdiffusion method. X-ray diffraction data to 2.3 Å resolution were collected using an orthorhombic crystal form belonging to space group P2 1 2 1 2 1 , with unit-cell parameters a = 76.55, b = 130.86, c = 170.87 Å . Str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
(23 reference statements)
0
5
0
Order By: Relevance
“…To obtain peptide-free DAP BII crystals 39 , the samples were crystallised using the hanging-drop method, in which 1 μl of protein solution (10 mg/ml DAP BII in 80 mM Tris-HCl, pH 8.5) was mixed with the same volume of reservoir solution (18% (w/v) PEG8000, 20% (v/v) glycerol, and 2 mM zinc chloride in 0.08 M CHES-NaOH, pH 9.5) and incubated at 293 K. The drops were suspended over 500 μl of reservoir solution in 24-well plates. Peptide-free crystals were also obtained using a counter-diffusion crystallisation method 40 under a microgravity environment in the Japanese Experimental Module “Kibo” at the International Space Station (ISS) 41 .…”
Section: Methodsmentioning
confidence: 99%
“…To obtain peptide-free DAP BII crystals 39 , the samples were crystallised using the hanging-drop method, in which 1 μl of protein solution (10 mg/ml DAP BII in 80 mM Tris-HCl, pH 8.5) was mixed with the same volume of reservoir solution (18% (w/v) PEG8000, 20% (v/v) glycerol, and 2 mM zinc chloride in 0.08 M CHES-NaOH, pH 9.5) and incubated at 293 K. The drops were suspended over 500 μl of reservoir solution in 24-well plates. Peptide-free crystals were also obtained using a counter-diffusion crystallisation method 40 under a microgravity environment in the Japanese Experimental Module “Kibo” at the International Space Station (ISS) 41 .…”
Section: Methodsmentioning
confidence: 99%
“…Recently, the first three-dimensional structure of a S46 peptidase has been determined, for DAP BII 31 32 . That study revealed that DAP BII is a homodimer and that each subunit contains a peptidase domain including a double β-barrel fold that is characteristic of the chymotrypsin superfamily 33 34 , as well as an unusual α-helical domain that regulates the exopeptidase activity of DAP BII.…”
mentioning
confidence: 99%
“…Assuming the presence of one subunit per asymmetric unit led to an empirically acceptable V M value of 2.79 Å 3 Da À1 , corresponding to a solvent content of 55.9% (Matthews, 1968). Since another S46 peptidase, bacterial DAP BII (Ogasawara et al, 1996;Sakamoto, Suzuki, Iizuka, Tateoka, Roppongi, Fujimoto et al, 2014;Sakamoto, Suzuki, Iizuka, Tateoka, Roppongi, Okada et al, 2014), was observed to be a dimer, we assume that PgDPP11 also forms a dimer. In that case, the molecular twofold axis of the dimeric PgDPP11 molecule must coincide with a crystallographic twofold axis of the C222 1 crystal of PgDPP11.…”
Section: Figurementioning
confidence: 99%
“…Initially, we tried to solve the structure of PgDPP11 by molecular-replacement techniques. Structures of DAP BII complexed with or without a peptide (Sakamoto, Suzuki, Iizuka, Tateoka, Roppongi, Okada et al, 2014), belonging to the S46 peptidase family (Suzuki et al, 2014) and having 29% sequence identity with PgDPP11, were used as search models. Since these attempts failed, a search for heavyatom derivatives intended for phasing by the multiple/single isomorphous replacement method and the preparation of selenomethionine-substituted PgDPP11 using LeMaster medium (Hendrickson et al, 1990) and E. coli B834(DE3) cells for phasing by Se-MAD/SAD methods are under way.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation